Applying the Bundle–Move Connection Approach to the Development of an Online Writing Support Tool for Research Articles. Issue 4 (28th August 2017) - Mizumoto, Atsushi; Hamatani, Sawako; Imao, Yasuhiro
Abstract: With advances in information and computer technology, genre‐based writing pedagogy has developed greatly in recent years. In order to further this growth in technology‐enhanced genre writing pedagogy, this study developed a data‐driven and theory‐based practical support tool for writing research articles. This web‐based, innovative tool, powered by a combination of rhetorical moves and lexical bundles, has an autocomplete feature that suggests the most frequent lexical bundles in a move within a research article section. This innovative web‐based tool was developed based on the proof of concept of the bundle–move connection approach. Preliminary user feedback was positive overall, and it was found that the writing support tool brought about beneficial effects that genre‐writing pedagogy explicitly aims to achieve. In light of these findings, pedagogical implications of the tool are discussed, with particular focus on the potential role that it could play in the teaching and learning of technology‐enhanced genre writing. Open Practices: This article has been awarded Open Materials and Open Data badges. All materials and data are publicly accessible via the IRIS Repository athttps://www.iris-database.org/iris/app/home/detail?id=york:932233 . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .